Binding of the Complexin N terminus to the SNARE complex potentiates synaptic vesicle fusogenicity - Xue, Mingshan (2010)
Complexins facilitate and inhibit neurotransmitter release through distinct domains, and their function was proposed to be coupled to the Ca(2+) sensor Synaptotagmin-1. However, the mechanisms underlying Complexin function remain unclear. We now uncover an interaction between the Complexin N terminus and the SNARE complex C terminus, and show that disrupting this interaction abolishes the facilitatory function of Complexins in mouse neurons. Analyses of hypertonically induced exocytosis demonstrate that Complexins enhance synaptic vesicle fusogenicity. Genetic experiments crossing Complexin and Synaptotagmin-1 null mice indicate a functional interaction between these proteins, but also show that Complexins can promote Ca(2+)-triggered release in the absence of Synaptotagmin-1. We propose that the Complexin N terminus stabilizes the SNARE complex C terminus and/or helps release the inhibitory function of Complexins, thereby activating the fusion machinery in a manner that may cooperate with Synaptotagmin-1, but does not require Synaptotagmin-1.